FAKTOR INTERNAL DAN EKSTERNAL DALAM PERKEMBANGAN USAHA KOPERASI DI KOTA MAGELANG - Siti Noor Khikmah (Universitas Ahmad Dahlan, 2013)
The purpose of this study was to test empirically that internal factors (member participation, solidarity among members, education and leadership management, business scale; capital development; managerial skills; market network, the number and quality of human resources; ownership and utilization of production technology and information; management system ; the performance of the board; similarity of interests of members) and external factors (government commitment; infrastructure systems; services, education and counseling; supporting climate; lifting of government facilities; price level) affect the development of cooperatives in the city of Magelang. The sample was 34 and the cooperative management that can be processed by 27 respondents. Analysis of the data used is multiple regression. Results of fieldwork states that the board of education and leadership has a positive effect on the development of a cooperative effort. This study can not prove the other internal factors and external factors affect the development of a cooperative effort. The test results of the adjusted R2 menghaslkan 34.9% while the remaining 65.1% is influenced by other fakor outside the research model.